Management of mandibular facial space infection of odontogenic origin - Bagamaspad, Arlene R.
Randy, a 16 years old boy was referred to the Pediatric Dentistry Division by the Emergency Room doctors due to the swelling on the lower right quadrant of the face. This is on the 8th day after he experienced the first pain on tooth #47. This paper aims to diagnose and treat appropriate infection involving the teeth and supporting structures, and recognize the clinicians capability and limitation to determine when professional consultation and/or patient referral is indicted.
Keywords: Diagnose; Consultation; Referral; Swelling